An efficient and broadly applicable method for transient transformation of plants using vertically aligned carbon nanofiber arrays - Morgan, Jessica M.; Jelenska, Joanna; Hensley, Dale; Retterer, Scott T.; Morrell-Falvey, Jennifer L.; Standaert, Robert F.; Greenberg, Jean T. (Frontiers in Plant Science, 2022)
We pioneered and demonstrated the use of vertically aligned carbon nanofiber (VACNF) arrays to efficiently perform transient transformation of different tissues with DNA constructs in multiple plant species. The VACNFs permeabilize plant tissue transiently to allow molecules into cells without causing a detectable stress response. We successfully delivered DNA into leaves, roots and fruit of five plant species (Arabidopsis, poplar, lettuce, Nicotiana benthamiana, and tomato) and confirmed accumulation of the encoded fluorescent proteins by confocal microscopy. Using this system, it is possible to transiently transform plant cells with both small and large plasmids. The method is successful for species recalcitrant to Agrobacterium-mediated transformation (demonstrated with the use of dye delivery in strawberries, peaches, and apples). VACNFs provide simple, reliable means of DNA delivery into a variety of plant organs and species.